The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3991/ijim.v14i12.15575
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Life-Based Learning Based Local Wisdom in the Development of Innovative Biotechnology Learning Models

Abstract: The development on biotechnology research is on the rapid growth. Biotechnology is assumed to be able to solve the needs problem in the community. University of Jember has developed a biotechnology research which focused on the fields of agricultural and health biotechnology. However, the result of biotechnology research has not been entirely integrated yet into the learning at schools, college, and community education. This research was intended to associate the products of biotechnology research with the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…It can be implemented in learning in the university level to make an integration between the learning materials between the student's daily experiences. It is in line with [17] revealed that the module is of the innovation for the integration of life-based learning in the development of innovative biotechnology learning that was valid, effective, and useful at the schools, university and the local community in East Java.…”
Section: Resultssupporting
confidence: 74%
“…It can be implemented in learning in the university level to make an integration between the learning materials between the student's daily experiences. It is in line with [17] revealed that the module is of the innovation for the integration of life-based learning in the development of innovative biotechnology learning that was valid, effective, and useful at the schools, university and the local community in East Java.…”
Section: Resultssupporting
confidence: 74%
“…Municipal wastewater is a mixture of multiple water qualities, which may contain industrial wastewater, domestic sewage, etc. The current severe shortage of water resources makes the process flow of municipal wastewater treatment particularly important [6]. Wastewater treatment generally requires five processing and treatment components, of which there are four main basic processing and treatment processes, as shown in Figure 1.…”
Section: Analysis Of Sewage Treatment Processmentioning
confidence: 99%
“…Combining the concept of biotechnology with local values will make it easier for students to understand the material, while increasing the relevance of learning to the context of students' daily lives. Thus, students not only acquire biotechnology knowledge, but also develop a love for culture and the surrounding environment (Suratno et al, 2020). By integrating life-based learning with local wisdom, innovative biotechnology learning models can be developed and applied in schools, universities, and communities (Buntting & Jones, 2020).…”
Section: Introductionmentioning
confidence: 99%